Analyzing The Effects Of The Health BPJS Regulation On The Insurance Companies Performance And Efficiency - Syefiki Amalia Army; Katiya Nahda (Publikasi Indonesia, 2023)
The purpose of this study was to determine the effect of the presence of BPJS Kesehatan regulations on the level of efficiency of insurance companies and to determine the effect of the level of efficiency of insurance companies on company performance in the period 2009 (before the implementation of the BPJS Kesehatan regulations) to 2019 (after the implementation of the BPJS Kesehatan regulations). The method used in this study is the analysis of Data Envelopment Analysis (DEA), calculation of Return on Assets (ROA), and calculation of Return on Equity (ROE) by testing 12 insurance company samples. The results showed that the company's efficiency had a significant positive change in the period before compared to after implementing the BPJS Kesehatan regulation. The tests of ROA and ROE showed that the company's performance did not significantly differ before and after implementing the BPJS Kesehatan regulation.